EXPERT SYSTEMS APPLICATION IN THE LABOUR SAFETY CONTROL SYSTEM AT THE ENGINEERING ENTERPRISES - S.A. SOLOD; V.V. NOVIKOV; E.S. CHAPOVA (Advanced Engineering Research, 2010)
Analysis of expert systems application in labour safety at the engineering enterprises which is used in decision-making support systems by the head of a department is considered. The efficiency of these systems is proved. Procedural chains of decision-making with flexible management strategies are presented.